2016
DOI: 10.1186/s12284-016-0080-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Evolutionary Analysis of Purple Leaf Sheath in Rice

Abstract: BackgroundAnthocyanin accumulates in many plant tissues or organs, in rice for example leading to red, purple red and purple phenotypes for protection from damage by biotic and abiotic stresses and for reproduction. Purple leaf, leaf sheath, stigma, pericarp, and apiculus are common in wild rice and landraces and occasionally found in modern cultivars. No gene directly conferring anthocyanin deposited in a purple leaf sheath has yet been isolated by using natural variants. An F2 population derived from ssp. ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 58 publications
(79 reference statements)
1
51
0
Order By: Relevance
“…Oikawa et al (2015) [50] identified Kala4 gene controlling anthocyanin biosynthesis, identical to OSB2 gene confirmed by Sakamoto et al (2001) [65] in rice. Chin et al(2016) [66] have showed that the OsC1 gene of chromosome 6 is related to the purple sheath in rice, encoding a MYB transcription factor. In this study, for the whole panel, a pericarp color-related QTL was detected, where the most significant SNP Chr1_22408336 was adjacent to the Rd [49] participating in the proanthocyanidins biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Oikawa et al (2015) [50] identified Kala4 gene controlling anthocyanin biosynthesis, identical to OSB2 gene confirmed by Sakamoto et al (2001) [65] in rice. Chin et al(2016) [66] have showed that the OsC1 gene of chromosome 6 is related to the purple sheath in rice, encoding a MYB transcription factor. In this study, for the whole panel, a pericarp color-related QTL was detected, where the most significant SNP Chr1_22408336 was adjacent to the Rd [49] participating in the proanthocyanidins biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Five putative anthocyanin biosynthesis regulators, including four bHLH genes Ra1 / OsB1 , Rb , Ra2 and OsB2 , and the R2R3‐MYB gene OsC1 , were isolated from rice through comparative mapping between rice and maize or according to the nucleotide sequence homology of known maize orthologues (Hu et al ., , ; Reddy et al ., ; Sakamoto et al ., ; Saitoh et al ., ). Genetic analysis demonstrated that OsC1 is the determinant factor of anthocyanin biosynthesis in leaf sheath and apiculus (Fan et al ., ; Chin et al ., ), and also a domestication‐related gene for the loss of anthocyanin accumulation in cultivated rice (Huang et al ., ). Rc , a bHLH gene, is the determinant factor for pro‐anthocyanidin biosynthesis in the pericarp (Sweeney et al ., ), and also a domestication‐related gene for the loss of pro‐anthocyanidin accumulation in cultivated rice (Sweeney et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, conflicting reports were also obtained by other researchers (Nagata, Yoshinaga, Takanashi, & Terao, ; Pan et al., ) who concluded that the amount of NSC accumulation in leaf sheaths at heading was not significantly affected by N application, despite a high increase in dry weight under heavy N application. According to Chin, Wu, Hour, Hong, and Lin (), the amount of NSC accumulation in leaf sheaths peaked around the heading date and then decreased gradually along with grain development. Under water deficient conditions, the translocation efficiency of NSC from leaf sheaths to grains markedly increased, but this occurrence was commonly accompanied by a shortened grain‐filling period as well as an accelerated senescence of functional leaves (Yang et al., , ).…”
Section: Introductionmentioning
confidence: 99%